Implementasi Manajemen Risiko Dalam Meningkatkan Mutu Tata Kelola Lembaga Pendidikan - Tondi Alvado; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
Risk management plays a crucial role in strengthening the quality of governance within educational institutions. In the context of increasing organizational complexity and accountability demands, educational institutions are exposed to various risks that may affect institutional performance and sustainability. This article aims to examine how the implementation of risk management contributes to improving governance quality in educational institutions. The study adopts a qualitative approach through a systematic literature review and descriptive analysis of risk management concepts and practices applied in the education sector. The results indicate that effective risk management implementation, encompassing risk identification, assessment, mitigation, and monitoring, supports better strategic planning, enhances internal control mechanisms, and promotes transparency in institutional management. Moreover, the integration of risk management helps institutions anticipate potential disruptions and optimize resource utilization. Therefore, risk management should be regarded as an integral component of good governance practices to ensure continuous quality improvement in educational institutions.